A Situation Judgment Test for Military Multicultural Decision-Making: Initial Psychometric Studies. (September 2016) - Reinerman-Jones, Lauren; Matthews, Gerald; Burke, Shawn; Scribner, David
Like other organizations with a global reach, the US military faces challenges associated with multicultural teaming. Cultural differences in norms for work and social relationships may impair decision-making. This article reports the initial stages of the development of a Situation Judgment Test (SJT) for multicultural decision-making ability. SJTs may have greater validity than self-reports of competence. An initial SJT was developed on the basis of critical incidents in multinational operations recounted by military Subject Matter Experts (SMEs). Study 1 examined psychometric properties of the SJT in an internet sample of 250 predominantly civilian respondents. Study 2 collected data from 61 US and coalition partner Warfighters participating in a joint exercise. Findings confirmed the reliability of the assessment across different populations, and established a gradation of item difficulty. Civilian and military samples show somewhat similar response patterns suggesting that multicultural decision-making may reflect shared Western values. Implications for assessment and training are discussed.